Onshore dating of Late Paleozoic through Mesozoic activities on the eastern and western proto-North Atlantic margins - Eide, Elizabeth A.; Torsvik, Trond H. (1998)
This report compiles results from six separate studies linked by the common fact that they address absolute dating of initiation and reactivation of brittle faults, dike emplacement and regional unroofing around the Rift region, clearly demonstrate mutual and specific tectonic associations for the Late Paleozoic and Mesozoic that were only previously inferred from available data. Precise age data show very connected and correlatable histories for these marginal proto-North Atlantic zones for early Carboni- ferous, Permian, early Triassic and middle Jurassic times. These regions have been cited in the literature for their import in constraining offshore tectonic and basin development, but the new data provide, for the first time, very quantitative results to pinpoint and interpret these events. 45161